نموذج الإدارة الالكترونية-مدخل استراتيجي لتعزيز استراتيجيات الريادة : دراسة حالة في شركة الحكماء لصناعة الادوية في مدينة الموصل - د. سعيد عبدالله محمد; عبدالعزيز طيب فتحي (PROSPECTIVE RESEARCHES, 2023)
The foundation of information and communication technology forms a base to adopt and implant electronic management paradigm. It has taken place as systematical and tidy managerial form, that involves all the organizational and substantial and humanly constituents in philosophy perspective. In any organization when the entrepreneur became on aim, enquiring by all coeval managers, to achieve sustainable and strategic success in global competition markets. The electronic management paradigm could be a strategic approach to enhance the entrepreneurship strategies, and gage their continence, that based on strategic concept in organization. From this point, we assume that recent research idea, seeks to study "Al-Hokamaa company for curatives in Mosul city" to search the current management paradigm, and compare it with electronic paradigm, to reach tolls that enhance the entrepreneurship, strategies for organization.